DOI: 10.1159/000396102
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Proteinuria

Abstract: Exercise-induced proteinuria? Urinalysis reveals an excessive level of protein, but your patient is a runner. How concerned should you be? CASE c As part of a routine physical examination, urinalysis reveals that a patient new to your practice is excreting an excessive level of protein. The patient is physically fit and shared during the history taking that he is an avid runner. The physical examination and other laboratory values were unremarkable. How concerned should you be about the finding of proteinuria?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Urinary protein creatinine ratios measuring protein by routine chemical methods have also been used but have not been widely adopted.18-20 It has probably been assumed that the protein content of a single urine sample could not accurately reflect total daily urinary excretion of protein because this fluctuates considerably during a 24 hour period, being reduced by recumbency or a high urine flow21 and increased by exercise. 22 We found the protein creatinine index on random specimens to be very sensitive: all patients excreting more than 150 mg protein a day had an index for random samples of more than 127. The index on early morning specimens was less sensitive and 15% of patients had results less than 108.…”
Section: Albustix Studiesmentioning
confidence: 81%
“…Urinary protein creatinine ratios measuring protein by routine chemical methods have also been used but have not been widely adopted.18-20 It has probably been assumed that the protein content of a single urine sample could not accurately reflect total daily urinary excretion of protein because this fluctuates considerably during a 24 hour period, being reduced by recumbency or a high urine flow21 and increased by exercise. 22 We found the protein creatinine index on random specimens to be very sensitive: all patients excreting more than 150 mg protein a day had an index for random samples of more than 127. The index on early morning specimens was less sensitive and 15% of patients had results less than 108.…”
Section: Albustix Studiesmentioning
confidence: 81%
“…Huttunen" and Campanacci et al 26 failed to find any increase in 11 2 -microglobulin excretion after exercise and Leiper et al 27 did not observe any change in NAG excretion during low intensity walks. On the other hand excretion of 11 2 -rnicroglobulin,'!…”
Section: Discussionmentioning
confidence: 93%
“…These studies have demonstrated that moderate physical activity induces an apparent abnormality in glomemlar permeability, manifest as an increase in the urinary excretion of albumin and other high molecular weight proteins (9,39). On the other hand, strenuous, exhaustive exercise appears to increase the urinary excretion of both albumin and lysozyme or B2-microglobulin, thus demonstrating both a "glomerular" and "tubular" pattern (9-1 1, 39).…”
Section: Discussionmentioning
confidence: 99%